Critical evaluation of the contractors's occupational safety and health (OSH) management system in the prevention of occupational accidents at Zimplats, Selous - Karikeka, Lameck (Midlands State University, 2015)
This study focused on the critical evaluation of contractors’ occupational safety and health (OSH) in managing accidents at workplace at Zimplats, Selous. The objectives of the study were to analyse causes of accidents in contractors, to evaluate establishment of contractor OSH system, evaluate establishment of contractor OSH management system, determine efficacy of the OSH management system in accidents reduction and to analyse the safety culture of contractors. A cross sectional survey design was employed and a sample of 172 contractor employees was selected. Questionnaires and semi structured intervals were self-administered to solicit data from contractor employees and key informants respectively. Observations coupled with taking photographs and retrospective review of data complemented the collection of valid and reliable data regarding analysis of OSH management system of contractors. Statistical package for social science (SPSS) was used to analyse quantitative and qualitative data. The study revealed that OSH management system is not effective and there is no safety culture among contractors. Furthermore, the main causes of accidents are production pressure, unsafe acts, inadequate risk assessment and inexperienced labour force. Also top contractors’ management is not visible and committed in safety and health programs to address issues coming from leading and lagging indicators. The study recommended the top management of contractors to accept full responsibility for safety and health and be role models. Furthermore, the principal company and contractors should harmonize safety systems through Job Hazard Analysis and on-site training to involve all part members. To relate production target to labour force so that production is direct proportional to a person per ton produced. Lastly but least the principal company to carry out periodic contractor assessment and auditing to keep contractors committed to the occupational management systems.